KONSTRUKSI IDENTITAS GASTRONOMI DALAM CITY BRANDING KOTA PADANG (STUDI PADA FASE AWAL ROAD TO GASTRONOMY CITY) - Rina Wahyuni; Yesi Puspita; M.A. Dalmenda (Jurnal Ranah Komunikasi, 2026)
Padang's culinary reputation has long been embedded deeply in public consciousness, yet this strong association has never been deliberately managed as a sustained city branding identity. This article examines how gastronomic identity is being constructed during the early phase of Padang's Road to Gastronomy City agenda, including the reasoning behind gastronomy's selection as the city's new identity direction. The study adopts a qualitative case study design within a social constructivist paradigm, drawing on two complementary analytical frameworks, namely Berger and Luckmann's (1966) social construction of reality and Kavaratzis and Hatch's (2013) dynamics of city identity. Data were gathered through semi-structured interviews with nine purposively selected informants from city government and the local gastronomy ecosystem, supported by observation and documentation, and analyzed thematically using NVivo 15. The findings reveal four simultaneous processes: the rearticulation of culinary reputation as symbolic capital, the expansion of culinary practice into gastronomy as a system of culture and experience, the differentiation of the city through an orientation toward international recognition, and the strengthening of the local economic ecosystem through micro, small, and medium enterprises, tourism, and the creative economy. Most significantly, the study identifies a communication gap between the identity expressed in official government narratives and the identity actually understood by the public, indicating that gastronomic identity construction in Padang remains at an early stage, layered with tensions that cannot be resolved through a single policy moment.